Relationship between the agronomic and anatomical characteristics of the leaf with a view to indirect selection in maize plants1 - do Nascimento-Júnior, Ivanildo Ramalho [UNESP]; Môro, Gustavo Vitti [UNESP]; Môro, Fabíola Vitti [UNESP] (GN1 Sistemas e Publicacoes, 2021)
In crops such as maize, the leaf is directly related to dry-matter accumulation in the grain, and directly affects plant yield. The aim of this study was to verify the existence of a correlation between the agronomic and anatomical characteristics of the maize leaf, as well as to verify the effects of these characteristics on grain production using path analysis. The agronomic characteristics used in the analysis were plant height, height of ear insertion, relative position of the ear, lodging, plant breakage and grain yield. The following anatomical characteristics were evaluated: total leaf area, thickness of the bulliform cells, thickness of the adaxial and abaxial epidermis, thickness of the mesophyll, area of the xylem, phloem and sclerenchyma, and mean area of the vascular bundles. In analysing the genotypic correlation, associations were seen at 1% significance between mesophyll thickness and plant height, mesophyll thickness and height of ear insertion, and mesophyll thickness and plant breakage, indicating the possibility of indirect selection for these agronomic characteristics. From the path analysis, it was found that the agronomic characteristics of lodging and breakage, and the anatomical characteristics of thickness of the adaxial epidermis, area of the xylem and area of the sclerenchyma had the greatest direct effect on grain yield, indicating the additional possibility of indirect selection for yield during the earliest stages of the plant. These results can afford faster selection of superior genotypes within the various breeding programs of the species.
Relação entre caracteres agronômicos e anatômicos da folha visando seleção indireta de plantas de milho
Keywords: Correlation. Association. Plant breeding. Zea mays L; Correlação. Associação. Melhoramento de plantas. Zea mays L